Application Value Stream Mapping to Minimize Waste in Aircraft Industry - Luciana, Livia; Lestari, Yuliani Dwi (Journal of Business and Management, 2015)
Abstract. Nowadays, many organizations have already implemented lean manufacturing (LM) in order to be competitive in global market. Â Many company need Lean Manufacture to reduce wastes or activity that has no added value to increasing efficiency in process production. Currently, PT Xis one of aircraft manufacturing in Indonesia has issues a procurement department. Currently, the big problem of procurement department is delays to make dokument PR and PO in 2014 this cause the long lead time in 2014.Based on historical data, total delay from making PR is very high about 84% and for PO the delay takes 73%. With these facts that procurement department has very high delay in making PR and PO, PT Xwants to solve this problem by identify waste that happen in procurement department, so it will decrease the lead time in procurement department. The first stage in the application of value stream mapping is the Current State Mapping, this stage can illustrates the real condition of procurement department processes along with lead time of any such process. The second stage is analysis current value steam mapping, in this stage all waste is identified and resolved. The final stage is, Future State Mapping in this process produce a new process and a new lead time. Based on current Value Stream Mapping, it is found three category wastes there are over processing, waiting time, and unnecessary movement (motion). The solution provided to reduce the waste are cleaned-up SAP data, standardization of writing material, format Quotation and RFQ, procurement check point and email reminders. Solution that has been given can minimize waste and lead time and will reflect in future state mapping. By making Future state value stream mapping based on the solutions that have been given can reduce the total lead time. Total lead time in procurement department was reduced by 39%. Total lead time can decrease 19 days with average lead time 49 days for the current VSM decrease into 30 days for future VSM.Keywords:Â Value Stream Mapping, Waste, Lead time, procurement department, Aircraft Industry